Micropropagación de teca (Tectona grandis L.f) - Abdelnour-Esquivel, Ana; Muñoz, Anabelle (My University, 2005)
Micropropagation of teak (Tectona grandis L.f.). Teak (Tectona grandis L.f.) is considered valuable due to the quality of its wood. The world level demand for the wood supported the establishment of commercial plantations. However, the quality of such plantations motivated the beginning of improvement programs for this tree species. The introduction of micropropagation or in vitro clonal propagation techniques (under laboratory conditions) in breeding programs and in the establishment of commercial plantations, offers numerous advantages, it allows the mass propagation of superior trees in a reduced time and spac e, making possible the conservation of the valuable genetic characteristics of these materials. Furthermore, this type of propagation allows the commercialisation and transportation of produced plants to far away places and countries with few customs restrictions and lower possibilities of material losses. During this study the possibility to propagate teak using micropropagation was demonstrated, and a basic methodology that permitted high percentages of successes in each step of the process was developed.
Keywords: Propagación clonal; Micropropagación; Cultivo in vitro; Propagación vegetativa; Tectona grandis